Low‐Cost Sensor‐Rich Fluidic Elastomer Actuators Embedded with Paper Electronics. (20th April 2020) - Yang, Tilo H.; Shintake, Jun; Kanno, Ryo; Kao, C. Robert; Mizuno, Jun
Abstract : Fluidic elastomer actuators (FEAs) are popular actuation ways in soft robotics due to their low cost and simple fabrication process. To realize intelligent soft robotic systems, real‐time monitoring of their deformation and interactions with surrounding objects including shape and proximity is important. Thus, integration of sensors into FEAs while considering cost reduction and mass production is required. Because paper features low cost and recyclability, herein, two paper‐based sensors, resistive strain sensors (RSSs) and capacitive proximity sensors (CPSs), are incorporated into FEAs as the strain‐limiting layers. The RSS exhibits the ability to detect the actuated bending angle with hysteresis ≈0.01% and high repeatability for 30 cycles. The RSS is also able to detect different object sizes being grasped by the FEA. In contrast, the CPS starts detecting object proximity 8 mm away from the sensor surface and functions well at various approaching speeds. The CPS is also capable of distinguishing objects of different materials by their permittivity. Finally, an intelligent soft gripper which carries these two sensors is demonstrated, where bending curvature, object proximity, contact, and release are monitored in real time. The results provide a pathway for the development of low‐cost sensorized soft robotic systems with advanced sensing functionalities. Abstract : A soft pneumatic actuator embedded with paper electronics that owns multifunctional sensing abilities to detect shape, proximity, and material properties is presented. Herein, a low‐cost and mass‐reproducible integration strategy paving the way for highly sensorized intelligent soft robotic systems is provided.